Analysis of the influence of satisfaction on consumer loyalty in standard rooms at Setia Hotel in Sintang District - Sari, Wulan Purnama; Lestari, Saodah Dwi (JURNAL MANAJEMEN MOTIVASI, 2018)
This study aims to know the influence of satisfaction on customer loyalty of standard rooms of Setia Hotel in Sintang District. Because moving in the field of services, then the hotel must provide a satisfactory service for consumers to be loyal. The population in this study were consumers who had stayed at the Hotel Setia Sintang, with a sample of 100 respondents. Sampling technique in this research uses purposive sampling method. Data of simple linear regression at analysis, coefficient, the coefficient of determination, and last test. The results of simple linear regression analysis show: = -0.388 + 1.050X. The coefficient result gives an R-value of 0.798 which means that the high is high between satisfaction (X) and loyalty (Y). Value (RSquare) of 0.637 or 63%. It shows that the independent variable (satisfaction) to the honest variable (loyalty) of 63% while the number of 37% or variable with others not included in this study. The loss test shows that the value of t () is 13.110 and Knowing of 1.98447 because it is bigger than then Ho is rejected. Thus, there is a positive relationship between satisfaction and loyalty of the standard hotel loyalty in Sintang Regency.